Characteristics of Abnormal Diffusivity in Normal-Appearing White Matter Investigated with Diffusion Tensor MR Imaging in Tuberous Sclerosis Complex - Makki, M.I.; Chugani, D.C.; Janisse, J.; Chugani, H.T. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Although patients with tuberous sclerosis complex (TSC) manifest various structural abnormalities, we hypothesized that white matter (WM) structures that appear normal on conventional MR imaging may be accompanied by microstructural changes, such as gliosis and myelinization defects. Our objective was to determine in vivo whether there was evidence for WM microstructural changes by using diffusion tensor imaging (DTI).MATERIALS AND METHODS: We used DTI to evaluate diffusivity and anisotropy in normal-appearing WM (NAWM) of 6 children with TSC and 12 age-matched control subjects. The anterior and posterior limbs of the internal capsule, the external capsule, and the genu and splenium of the corpus callosum were assessed. We hypothesized that previously reported DTI abnormalities of NAWM in patients with TSC may not be equal in all diffusion directions as measured by the major, middle, and minor eigenvalues.RESULTS: When combining NAWM regions in patients with TSC, we observed a significant increase in mean diffusivity (P = .003) and a decrease in anisotropy (P = .03) compared with those of controls. However, the increase in diffusivity was more pronounced in directions orthogonal to the axons measured by the minor and middle eigenvalues (P = .005) than by the major eigenvalue (P = .02).CONCLUSION: Our findings revealed a decrease in anisotropy and an increase in longitudinal and radial diffusivities in NAWM beyond the location of TSC lesions seen on conventional MR imaging. The axonal microstructural changes suggested by our study may be related to changes in myelin packing due to giant cells accompanied by gliosis and myelination defects known to occur in TSC WM.